In-Situ Hydrothermal Synthesis of Bi–Bi2O2CO3 Heterojunction Photocatalyst with Enhanced Visible Light Photocatalytic Activity - Kar, Prasenjit; Maji, Tuhin Kumar; Nandi, Ramesh; Lemmens, Peter; Pal, Samir Kumar (Nano-Micro Letters, 2016)
Bismuth containing nanomaterials recently received increasing attention with respect to environmental applications because of their low cost, high stability and nontoxicity. In this work, Bi–Bi2O2CO3 heterojunctions were fabricated by in-situ decoration of Bi nanoparticles on Bi2O2CO3 nanosheets via a simple hydrothermal synthesis approach. X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high-resolution TEM (HRTEM) were used to confirm the morphology of the nanosheet-like heterostructure of the Bi–Bi2O2CO3 composite. Detailed ultrafast electronic spectroscopy reveals that the in-situ decoration of Bi nanoparticles on Bi2O2CO3 nanosheets exhibit a dramatically enhanced electron-hole pair separation rate, which results in an extraordinarily high photocatalytic activity for the degradation of a model organic dye, methylene blue (MB) under visible light illumination. Cycling experiments revealed a good photochemical stability of the Bi–Bi2O2CO3 heterojunction under repeated irradiation. Photocurrent measurements further indicated that the heterojunction incredibly enhanced the charge generation and suppressed the charge recombination of photogenerated electron-hole pairs. Highlights: 1 A facile low cost hydrothermal technique was employed to synthesize of Bi-Bi2O2CO3, and Bi nanoparticles was decorated in-situ on Bi2O2CO3. 2 The heterostructure exhibits enhanced electron-hole separation and improves visible-light photocatalytic activity effectively.